A Fast Convergent Approximation Method for the Solution of Second Order Linear Ordinary Differential Equations - Grigorian, Gevorg A. (Sarajevo Journal of Mathematics, 2024)
The Riccati equation method is used to obtain a fast convergent approximation method for the solution of second order linear ordinary differential equations. By using examples it is shown how fast the proposed method can converge.